A targeted rural postgraduate education programme – linking rural doctors across New Zealand and into the Pacific. Issue 6 (2nd November 2017) - Blattner, Katharina; Nixon, Garry; Gutenstein, Marc; Davey, Emma
Abstract: This article describes the University of Otago Rural Postgraduate medical programme, established in 2002 to provide a targeted rural education option for medical practitioners working in rural and remote areas of New Zealand. With both faculty and participants dispersed throughout New Zealand and the Cook Islands embedded in day to day rural clinical practice, this programme uniquely reflects the national and international clinical networks it has been developed to support. It now provides the academic component of two vocational training programmes: the New Zealand Rural Hospital Medicine Training Programme and The Cook Islands General Practice Training Programme. We describe the journey the Rural Postgraduate programme has taken over the last decade: the opportunities, learnings and challenges. The programme is continuing to expand and is creating a growing community of rural and remote practitioners throughout New Zealand and the Pacific.